Optimization of enzyme pre-treatment variables using response surface methodology for oil palm empty fruit bunches soda-aq pulp yield / Rushdan,I. ...[et al.] - I., Rushdan; M.B., Nurul Husna; J., Latifah; M., Ainun Zuriyati (2008)
The major disadvantage of conventional chemical pulping processes is the consumption of large amount of energy and chemical treatments. One of the methods to decrease the utilization of energy and chemical treatments is by biopulping. However little information is available on biopulping ofoil palm biomass - empty fruit bunch fibre (EFB). The main objective of this study is to determine the effect of enzyme on pulp yield. The EFB was treated with a commercial enzyme (Novozymes) at various dosage (A), pH (B) and retention times (C). The effects of enzymatic pretreatment variables were examined and analyzed using statistical experimental design response surface methodology (RSM) utilizing the central composite design (CCD) approach. In order to facilitate the analyses, statistical software DESIGN-EXPERT of Stat-Ease, Inc. USA was used to optimize the above-mentioned three parameters. After pre-treatment, the EFB was pulped by soda-anthraquinone pulping process. Comparison was done between treated and untreated pulping. The yields were in the range of 48 to 53%. The preliminary results show that pretreatment improved pulp yield (maximum up to 4%). The optimum conditions to produce a high screened yield at lowest dosage, natural pH and shortest retention time were as follows A = 5%, B = 6.5 pH and C = 6 hours.